Effects of the Neoflavonoid Coutareagenin, One of the Antidiabetic Active Substances of Hintonia latiflora, on Streptozotocin-induced Diabetes mellitus in Rats - Koreca, Rudolf; Senschb, Karl Heinz; Zoukasb, Thomas (Arzneimittelforschung, 2000)
In the present study, diabetes mellitus was induced with streptozotocin in Wistar rats from the inbred strain F > 28, and a blood sugar lowering effect due to the oral or intragastric administration of a copalchi native extract (Hintoniae latiflorae cortex) or intragastric administration of the pure substance, coutareagenin (neoflavonoid) (5-hydroxy-7-methoxy-4-(3,4-dihydroxyphenyl)-2H-benzo-1-pyran-2-on), was demonstrated with statistically significant results.This study enlarged and confirmed the results of earlier studies by other authors with regard to the antidiabetic effect of the copalchi bark extract in various animal species with hyperglycemia induced by different methods. By the use of the synthetically produced neoflavonoid, coutareagenin, the present series of tests provided evidence that coutareagenin, one of the active substances contained in Hintonia latiflora bark (Copalchi bark), produces a reduction of diabetic elevated blood sugar levels. The native extract as a whole, however, has to be regarded as the active substance (active substance complex) of Hintonia latiflora (Copalchi) bark.
Keywords: Antidiabetics; Copalchi bark; Coutareagenin, rat, reduction of elevated blood sugar; Hintonia latiflora; Neoflavonoid